2017
DOI: 10.24908/pceea.v0i0.7365
|View full text |Cite
|
Sign up to set email alerts
|

PUZZLE-BASED LEARNING: AN APPROACH TO CREATIVITY, DESIGN THINKING & PROBLEM SOLVING. IMPLICATIONS FOR ENGINEERING EDUCATION.

Abstract: -This paper will explore research practices already being conducted in various institutions, strengthening this paper's position that puzzle-based learning is a foundational methodology which assists newly admitted undergraduate engineering students, how to best approach critical problem solving. Furthermore, this paper will provide recommendations for an introductory protocol to introduce the incorporation of puzzle-based learning into a seminar-style course for First Year Introductory Engineering, and as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Sudoku can be a mental challenge and a satisfying accomplishment when completed. Learning how to solve puzzles is a great approach to stimulate creativity and to lay the foundation for young children to become effective problem solvers in real-life situations (Tudor-Hart, 1955;Costa, 2017). Engaging in puzzle-solving activities can offer various advantages.…”
Section: Masten (2014)mentioning
confidence: 99%
“…Sudoku can be a mental challenge and a satisfying accomplishment when completed. Learning how to solve puzzles is a great approach to stimulate creativity and to lay the foundation for young children to become effective problem solvers in real-life situations (Tudor-Hart, 1955;Costa, 2017). Engaging in puzzle-solving activities can offer various advantages.…”
Section: Masten (2014)mentioning
confidence: 99%
“…The authors reported that the PBL approach followed in performing a creative drama play which positively affected learners' self-efficacy abilities. While puzzle-based learning inherently solves a problem, the aim is to get learners to find solutions to unstructured problems (Michalewicz, Falkner & Sooriamurthi 2011) and, in the process of learning, help develop learners' thinking skills and problem-solving skills (Costa 2017).…”
Section: Problem-based Learning and Pedagogies Of Playmentioning
confidence: 99%